Penggunaan teknologi digital dalam kajian hadis - Luthfi Hidayah Nur'aini (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
Hadith studies are a crucial field in Islamic scholarship, requiring meticulous methods for validating and verifying the matan (text) and sanad (chain of transmission). With the advancement of time, digital technology has significantly impacted various fields of knowledge, including hadith studies. The use of digital technology, such as hadith software, digital databases, and text search applications, has facilitated the process of collecting, classifying, and analyzing hadith. This technology enables quick access to primary hadith sources scattered across different locations, and it helps researchers analyze both sanad and matan more efficiently. This study aims to examine how digital technology is used in various aspects of hadith studies, such as data collection, information management, and the verification of sanad and matan authenticity. It also explores the benefits and challenges faced by scholars and researchers in utilizing this technology, including the role of hadith software and digital databases in enhancing academic research. The study concludes that while digital technology offers significant advantages in improving the efficiency and accuracy of hadith studies, challenges related to data accuracy, information management, and accessibility still require further attention.